Independent Predictors of In-Hospital Mortality in Elderly and Non-elderly Adult Patients Undergoing Emergency Admission for Hemorrhoids. Issue 5 (May 2022) - Levy, Lior; Smiley, Abbas; Latifi, Rifat
Background: The study explored determinants of mortality of admitted emergently patients with the primary diagnosis of hemorrhoids, during the years 2005-2014. Methods: Demographics, clinical data, and outcomes were obtained from the National Inpatient Sample, 2005-2014, in elderly (65+ years) and non-elderly adult patients (18-64 years) with hemorrhoids who underwent emergency admission. Multivariable logistic regression model with backward elimination was used to identify predictors of mortality. Results: 25 808 adult and 26 978 elderly patients were included. Female patients consisted of 42.5% and 59.3% in adult and elderly, respectively. 42 (.2%) adults died, of which 50% were female and 125 (.5%) elderly patients died, of which 60% were female. Mean (SD) age of the adult patients was 47.8 (11) years and in elderly patients was 78.7 (8) years. 82.2% and 85.7% had internal hemorrhoids in adult and elderly patients, respectively. 9326 (36.1%) adult and 7282 (27%) elderly patients underwent an operation. In the final multivariable logistic regression model for adult patients with operation, delayed operation and invasive diagnostic procedures increased the odds of mortality, whereas in elderly patients, delayed operation and frailty index were the risk factors of mortality. In both adults and elderly with no operation, increased hospital length of stay (HLOS) significantly increased the odds of mortality, and undergoing an invasive diagnostic procedure significantly decreased the odds of mortality. Conclusion: In all operated patients, increased time to operation and undergoing an invasive diagnostic procedure were the risk factors for mortality. On the other hand, in non-operated emergency hemorrhoids patients, increased age and increased HLOS were the risk factors for mortality while undergoing an invasive diagnostic procedure decreased the odds of mortality.